Multiculturalism without culture - Phillips, Anne, 1950- (Princeton University Press, 2007)
Public opinion in recent years has soured on multiculturalism, due in large part to fears of radical Islam. In Multiculturalism without Culture, Anne Phillips contends that critics misrepresent culture as the explanation of everything individuals from minority and non-Western groups do. She puts forward a defense of multiculturalism that dispenses with notions of culture, instead placing individuals themselves at its core. Multiculturalism has been blamed for encouraging the oppression of women--forced marriages, female genital cutting, school girls wearing the hijab. Many critics opportunisti.